2021
DOI: 10.1016/j.jid.2020.08.013
|View full text |Cite
|
Sign up to set email alerts
|

Paired Transcriptomic and Proteomic Analysis Implicates IL-1β in the Pathogenesis of Papulopustular Rosacea Explants

Abstract: Papulopustular rosacea (PPR) is a chronic inflammatory skin disease with limited treatment options. Although multiple pathways have been described to be upregulated in PPR, a mechanistic understanding of the key drivers and interaction between pathways in PPR pathology is lacking. In this study, we utilized PPR skin biopsy explants to integrate both differentially expressed genes and differentially expressed proteins in paired nonlesional and lesional PPR tissue (n ¼ 5 patients). The results of this study iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
47
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(49 citation statements)
references
References 39 publications
0
47
2
Order By: Relevance
“…Together, these findings suggest an important role for IL-1b in the pathogenesis of PPR. To test this hypothesis, Harden et al (2020) performed an ex vivo experiment in which they exposed nonlesional skin from individuals with PPR to exogenous IL-1b and then quantified gene and protein expression. Compared with baseline, Harden et al (2020) found that exposure to IL-1b induced similar transcriptomic and proteomic changes to what they observed in PPR tissues.…”
Section: Discussion Of Incorrect Answersmentioning
confidence: 99%
See 4 more Smart Citations
“…Together, these findings suggest an important role for IL-1b in the pathogenesis of PPR. To test this hypothesis, Harden et al (2020) performed an ex vivo experiment in which they exposed nonlesional skin from individuals with PPR to exogenous IL-1b and then quantified gene and protein expression. Compared with baseline, Harden et al (2020) found that exposure to IL-1b induced similar transcriptomic and proteomic changes to what they observed in PPR tissues.…”
Section: Discussion Of Incorrect Answersmentioning
confidence: 99%
“…Papulopustular rosacea (PPR) is a chronic inflammatory syndrome characterized by a combination of erythema, telangiectasias, papules, and pustules; increased skin sensitivity; and thickening or phymatous changes of the skin (Gallo et al, 2018;Harden et al, 2020;Marson and Baldwin, 2020). These symptoms primarily present in a centrofacial distribution, which includes the cheeks, chin, nose, and middle forehead (Gallo et al, 2018).…”
Section: Detailed Answersmentioning
confidence: 99%
See 3 more Smart Citations